Trash to cash through permaculture for sustainable island tourism: the case of Semporna, Sabah, Malaysia - Siow, May Ling; Ramachandran, Sridar; Maizan, Kamarul Ariffin (Inderscience, 2022)
The objective of this paper is to employ an evidence-based intervention through permaculture practices on island tourism in Mabul, Semporna Sabah. Through the trash to cash initiative conducted over a span of two years in Mabul, this paper aims to identify the best practices and limitations of permaculture practice on an island, as well as to uncover lessons for future pursuits. This intervention was conducted in the Borneo Jungle River Island Tours Sdn. Bhd company for two years to identify usable permaculture methods for island-based lodges. A case study design was chosen for this purpose as it allows numbers of small in-depth cases conducted throughout the course of two years. These cases were studied in a real-life context, applying permaculture principles while observing how they influence and are influenced by users. Using permaculture principles, a total of ten different initiatives were coined and tested on-site. Top initiatives included: 1) collection of air-conditioner water; 2) composting; 3) environmental education. The major managerial challenges found were: 1) receptiveness of the initiative by workers; 2) change of mindset; 3) top-down initiatives. Borneo Jungle successfully reduced its costs and waste through this initiative.